Coleta seletiva e inclusão social: desafios da gestão pública municipal no sul de Minas Gerais - Carvalho, Tatiana Vilela (2016)
The practice of selective collection in partnership with associations of wastepickers (AW) is specified in the National Solid Residue Policy (PNRS). However, it is still a challenge to coordinate the management of these services in the municipalities, with the social inclusion of the wastepickers. The objectives of this research are to describe how the selective collection has been implemented in the municipality of Três Corações regarding the management of urban solid residue (USR), and the implementation of the PNRS. We also sought to demonstrate the reality of the municipalities of southern Minas Gerais, Brazil, which are a part of the Regional Environment Superintendence of Southern Minas Gerais (SUPRAM Sul), in order to situate and characterize the reality of Três Corações, considering the universe of the research according to a broader reality. For this, we conducted a survey of the public policies supporting the wastepickers at a Federal level, as well as in the state of Minas Gerais. We also conducted a descriptive data analysis of the situational questionnaire of selective collection applied by the Environment State Foundation (FEAM) in the years of 2014 and 2015. Data were surveyed by means of participant observation, document analysis, report analysis, searches in governmental websites, and participation in meetings and seminars. The data analysis was done by method triangulation, seeking the articulation between the collected information. The categories of analysis in relation to the municipalities presenting selective collection in partnership with the AW were: selective collection operation; institutional implementation support and expansion of the selective collection; selective collection management and difficulties in selective collect ion. We verified that it is essential that the City Hall monitor the selective collection indicators and the achievement of goals of the Residue Management Plans, given that the greatest issue presented in the municipalities is the low participation of the population. Specifically in Três Corações, alternatives must be created for the destination of organic residues. We concluded that external partnerships are essential to performing selective collection in partnership with the AW. The prominence of the par tnership of the Nenuca Institute of Sustainable Development (INSEA) in the municipalities of southern Minas Gerais became clear. The accompaniment of functionality indicators of the selective collection program must be conducted by the City Halls , in order to ensure the efficiency of the programs.